(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Student Motivation is one of the most important methods for Academic Achievement. It’ll give them the energy, reason, and inspiration to attain their goals. The poor structure and distribution of rewards discourages student. Also, unmotivated students might distract other students from academics by affecting their grades. To be able to solve the problem of learning, let’s have a positive mindset in every trial that comes in life, let everything be a lesson to us every day, and in times when we face a problem, this will test our ability to cope up, and here you can prove yourself when you have attained the highest grades. Here, you can think that you are capable and will motivate yourself that regardless of problems that come your way, you will be more capable of reaching your goals in life. This research study used a Qualitative method. To collect data needed to prove the Student Motivation for the Academic Achievement of Grade 12 Humanities and Social Sciences Students, the researchers provided a survey questionnaire of sixty (60) Humanities and Social Sciences honoured students of Bestlink College of the Philippines. The researchers used Likert Scale, Frequency and Percentage Distribution and Weighted Mean for the statistical data treatment. The primary purpose of this study is to prove the Importance of Motivation to the Academic Achievement of Grade 12 Humanities and Social Sciences Students of Bestlink College of the Philippines. It has been proven that Student Motivation is Important for Students to learn because it’ll help them to enhance their Academic Achievement. Motivation is important because it stops asking questions and aligns you to work towards your goals/dreams. Motivation is important for students so that they take the courage to move forward in life or to stepping stones toward their dreams; you need motivation to keep you chugging along your dreams, and motivation is not only important in its own right; it is also an important predictor of learning and achievement. Students who are more motivated to learn to persist longer, produce higher quality effort, learn more deeply, and perform better in classes and on standardized tests. (Terasolartisans, n.d.)